Indonesian post-migrant workers: A challenging problem for human security - Ali Maksum (Elsevier, 2021)
States benefit financially from the remittances received by “remittance heroes,” yet migrant workers are constantly in a precarious position, especially when their contracts expire and they return to their home countries. Scholars of migration and mobility studies tend to focus on two key issues: host country policies and migrant worker return processes, rather than post-migration issues. At the same time, the mainstream theories of International Relations (IR), especially realism and liberalism, have shown little interest in studying the situation of post-migrant workers, which is an issue that necessitates affirmative policy. Therefore, this essay argues that human security provides a broader approach through which to examine post-migrant workers' problems compared to IR mainstream theories, especially in the post-Cold War era. Although the human security approach is becoming increasingly accepted, the state-centred approach remains influential among migration scholars. As a result, discourse about post-migrant workers is still absent among policymakers in Indonesia while the state consistently enjoys remittance from what the state hails as “remittance heroes.” This preliminary research draws on established literature and secondary sources, such as scholarly studies, reports from international organisations, and news coverage. This essay ends with a policy recommendation.